A comparison on failure pressures of cylindrical pressure vessels - Gueven, Ugur (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
In this work, the failure pressures of thick and thin walled cylindrical pressure vessels considering the Voce hardening law and plastic orthotropy effect are obtained. The solution presented is used to compare the failure pressures of copper and brass cylindrical pressure vessels. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: cylindrical pressure vessels; failure pressure; large deformation; voce hardening law; plastic orthotropy; Mechanics